Method for recovering nitrogen and phosphorus in wastewater by using diatomite-based three-dimensional structure nano magnesium silicate
By using diatomaceous earth-based three-dimensional structure nanomagnesium silicate as adsorbent, the problem of removing nitrogen and phosphorus pollutants in water bodies is solved, efficient adsorption and recovery of nitrogen and phosphorus is achieved, and it is converted into slow-release fertilizer, realizing water body management and The dual goal of resource utilization.
Patent Information
- Application Number
- CN202411671389.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-21
- Publication Date
- 2025-02-18
AI Technical Summary
The prior art is difficult to effectively remove nitrogen and phosphorus pollutants in water bodies, especially in domestic wastewater with low nitrogen and phosphorus concentrations. Traditional methods such as MAP methods have problems with recycling difficulties and limited economic feasibility.
The adsorption and recovery of nitrogen and phosphorus in wastewater is achieved by adjusting the pH value of wastewater and adding diatomaceous earth-based nanomagnesium silicate. The method includes adjusting the pH of the wastewater to 8-9, adding celite-based nanomagnesium silicate and stirring for 0.5-3 hours, followed by filtration to complete the adsorption recovery of nitrogen and phosphorus.
It realizes efficient removal of nitrogen and phosphorus in wastewater, and obtains N, P, Si-rich magnesium phosphate/magnesium silicate composite materials rich in N, P, Si, and further applies to the preparation of slow-release fertilizers, solving the problem of nitrogen and phosphorus contamination of water bodies. Issues of governance and resource utilization.
Smart Images

Figure CN119461401A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of materials and solid waste resource recycling, and specifically relates to a method for recovering nitrogen and phosphorus in wastewater by using diatomaceous earth-based three-dimensional structure nano magnesium silicate. Background Art
[0002] Excessive discharge of wastewater with excessive nitrogen and phosphorus content will cause eutrophication of water bodies and groundwater pollution. The deep treatment of nitrogen and phosphorus in wastewater is a difficult problem that needs to be solved urgently. The sources of nitrogen and phosphorus pollution in natural water bodies are widespread. Nitrogen and phosphorus fertilizers applied by the planting industry, agricultural waste, domestic sewage, and industrial wastewater such as papermaking, leather making, printing and dyeing, and food discharged into water bodies will cause nitrogen and phosphorus pollution in water bodies. Generally speaking, when the total phosphorus and total nitrogen in the water body exceed 0.05 mg / L and 1.0 mg / L respectively, the water body is considered to be in a state of mild eutrophication. The precipitation method of adding magnesium salts to generate magnesium ammonium phosphate (MAP) is currently a commonly used method, but the resulting magnesium ammonium phosphate has small grains and is difficult to recover. Moreover, the MAP method is only effective when N(NH4 + )、P(PO4 3- ) exist at the same time and the concentration is greater than 50 mg / L. For domestic wastewater with low N and P concentrations, the adsorption method is not limited by the above factors. The adsorption method can not only make the polluted water meet the discharge standards, but also the adsorption recovery product can be used as fertilizer in rural planting industry because it is rich in N and P plant nutrients. Its low cost, high selectivity and simple operation have received continuous attention in the field of N and P polluted water treatment. Adsorbent is the key to the adsorption method. Therefore, the low-cost development of high-efficiency N and P adsorbents for the treatment of N and P polluted water bodies is of great significance to the water ecological environment and the resource utilization of solid waste.
[0003] At present, the main adsorbents used for the removal of N and P in water bodies are metal oxides / hydroxides; layered double hydroxides (LDH); zeolites; biochar and its composites, etc. Among them, there are relatively many studies on the removal of N and P based on metal oxides / hydroxides such as Al, Ca, Fe, La, Zn, and Mg. The adsorption mechanism of N and P pollutants in water bodies on metal oxides includes: electrostatic attraction between oxygen anions and protonated hydroxyls; ligand exchange to form covalent bonds between phosphates and metal cations (inner sphere surface complexation); and strengthening through hydrogen bonds between phosphates and H and O in metal oxides. Nano-metal oxides and hydroxides have good adsorption properties for negatively charged phosphates due to zeta potential, but for positively charged NH4 +The removal effect is not good. MgO / Mg(OH)2-based adsorbents can synergistically remove N and P from water bodies through the MAP method due to their rich Mg adsorption sites. The generated magnesium ammonium phosphate is an efficient N and P composite fertilizer. Nano-metal oxides / hydroxides such as nano-MgO / Mg(OH)2 have good effects on the removal of N and P from water bodies, but are limited by the difficulty in separation caused by small particle size, which limits their large-scale application. Loading MgO / Mg(OH)2 with high reaction activity on the surface of magnetic materials or relatively large micron-sized clay mineral materials are two common strategies. Mg-containing adsorption sites play a key role in the above materials, but the matrix in the composite material often only plays a role in preventing agglomeration and facilitating separation, which is not suitable for later use as a slow-release fertilizer. There are relatively few studies based on mineral materials as efficient N and P adsorption materials. Therefore, the design and preparation of Mg-containing mineral adsorbents that are easy to separate from water bodies is of great significance for the resource-based disposal of N and P-contaminated wastewater. Summary of the invention
[0004] In view of the above problems existing in the prior art, the present invention provides a method for recovering nitrogen and phosphorus in wastewater by using diatomite-based three-dimensional structure nano magnesium silicate.
[0005] Diatomite is amorphous silicon dioxide with a natural three-dimensional structure of uniform shape and size. Therefore, research based on diatomite has always been a hot topic in environmental remediation. The present invention uses cheap diatomite as a self-sacrificial template to convert low-grade diatomite with low specific surface area and low reactivity into a three-dimensional structure of chlorite phase magnesium silicate (Mg6Si4O 10 (OH)8). Chlorite phase magnesium silicate has a complex three-dimensional structure and a large specific surface area while being synthesized at low cost. It can remove N and P pollutants from water bodies by electrostatic attraction, complexation and crystallization precipitation. Chlorite phase magnesium silicate has a layered structure with a negatively charged 2:1 structural unit layer Mg3Si4O 10 (OH)2 interlayer Mg 2+ The ions can be separated from the interlayer due to the weak constraint of the silicon-oxygen tetrahedral layer, while the Mg in the positively charged octahedral sheet Mg3(OH)6 2+ Ions can also be separated from the structure and then react with NH4 + PO4 3- The reaction generates magnesium ammonium phosphate. The final adsorption product magnesium ammonium phosphate / magnesium silicate is rich in three plant nutrient elements: N, P and Si, and is expected to become a cheap N, P, Si composite slow-release fertilizer, thereby truly realizing the resource utilization of solid hazardous waste.
[0006] The method for recovering nitrogen and phosphorus from wastewater by using diatomite-based three-dimensional structure nano magnesium silicate of the present invention comprises the following steps: The pH value of the wastewater containing nitrogen and phosphorus is adjusted to 8-9; diatomaceous earth-based three-dimensional structure nano magnesium silicate is added to the wastewater after the pH value is adjusted, stirred for 0.5-3h, and filtered to complete the adsorption and recovery of N and P in the solution wastewater.
[0007] Furthermore, the nitrogen-phosphorus concentration ratio in the wastewater is 1:0.5-2, preferably 1:0.8-1.2.
[0008] Nitrogen in wastewater (NH4 + ) concentration ≤100 mg / L, phosphorus (PO4 3- ) When the concentration is ≤100 mg / L, the dosage of diatomite-based three-dimensional structured nano magnesium silicate is 0.3-0.7 g / L; when the nitrogen and phosphorus concentrations in the wastewater are 1000 mg / L>100 mg / L, the dosage of diatomite-based three-dimensional structured nano magnesium silicate is 0.7-3 g / L.
[0009] Furthermore, after filtering, the filter residue is dried to obtain a magnesium ammonium phosphate / magnesium silicate composite material rich in the three elements of N, P and Si, which is further used in the preparation of slow-release fertilizers containing nitrogen, phosphorus and silicon.
[0010] The diatomite-based three-dimensional structured nano magnesium silicate is prepared by using cheap diatomite as a self-sacrificial template to prepare chlorite phase magnesium silicate with high specific surface area and unique three-dimensional structure. The preparation process includes the following steps: Step 1: Add diatomaceous earth into ammonia water and stir to form a diatomaceous earth and ammonia water suspension; Step 2: dissolving magnesium chloride in deionized water, and slowly adding the obtained magnesium chloride solution dropwise to the suspension obtained in step 1 to obtain a mixed suspension; Step 3: The mixed suspension obtained in step 2 is aged for 6 to 10 hours under hydrothermal conditions at 180 to 200° C., cooled, washed, filtered, and dried to obtain diatomaceous earth-based three-dimensional magnesium silicate.
[0011] Preferably, in step 1, the volume ratio of ammonia water (25% wt) to the mass ratio of diatomaceous earth is 30-40:1 mL / g. Partial ionization of ammonia water provides an alkaline environment required for the reaction. When there is too much ammonia water, the diatomaceous earth is dissolved too quickly and cannot act as a template. When there is too little ammonia water, the reaction is not complete.
[0012] Preferably, in step 2, the mass ratio of MgCl2·6H2O to diatomite is 5 to 8:1. When the amount of magnesium chloride added is too much, the product is a mixture of chlorite phase magnesium silicate and magnesium hydroxide. When the amount of magnesium chloride added is too little, the magnesium content in the product is low, which is not conducive to the removal of N and P in the water body, thereby affecting the formation of magnesium ammonium phosphate.
[0013] The present invention uses cheap diatomite as a self-sacrificial template. On the one hand, diatomite provides silicate for the formation of magnesium silicate; on the other hand, the prepared magnesium silicate uses diatomite as a template, which replicates the morphological characteristics of diatomite and is self-assembled by nano-flower spherical magnesium silicate. The complex three-dimensional structure makes the prepared three-dimensional structure magnesium silicate have a relatively large specific surface area (287m 2 / g), which is beneficial to the high-performance removal of nitrogen and phosphorus pollutants in water. In the preparation process, the mass ratio of magnesium chloride and diatomaceous earth plays an important role. When the mass ratio is 1-3:1, the material morphology is flaky and fibrous; when the mass ratio is 5-8:1, it will form a flower ball shape. The physical phase of synthetic magnesium silicate is different due to different mass ratios. Compared with the preparation methods of other three-dimensional structural materials, the synthesis process of the present invention is simple, the price of diatomaceous earth self-sacrificial template is low, no surfactant needs to be added during the synthesis process, and the cost is low.
[0014] The diatomite-based magnesium silicate prepared by the present invention has a large specific surface area, a three-dimensional structure, and is rich in magnesium hydroxyl groups (Mg-OH) on the surface, and can remove N and P pollutants in water bodies by physical adsorption and chemical adsorption. 2+ Ions can be separated from the silicon-oxygen tetrahedral layer of magnesium silicate and enter N, P wastewater and NH4 + PO4 3- The reaction generates magnesium ammonium phosphate, which is coated on the surface of spherical magnesium silicate or exists in micron-sized blocks or rods. The magnesium ammonium phosphate / magnesium silicate composite material finally obtained can slowly release N, P, Si plant nutrients in water or soil, and is a slow-release fertilizer with good performance.
[0015] The method of the present invention is suitable for treating industrial and agricultural wastewater and eutrophic water bodies with excessive ammonia nitrogen and phosphate at the same time or one of them. The obtained product can be used as a slow-release fertilizer, which has the advantages of energy saving and green environmental protection. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1 This is the X-ray diffraction curve of diatomaceous earth-based magnesium silicate prepared in Example 1.
[0017] Figure 2 These are scanning electron microscope photos of diatomaceous earth-based magnesium silicate prepared in Example 1, where (A) and (B) are at different magnifications.
[0018] Figure 3 This is the X-ray diffraction curve of diatomaceous earth-based magnesium silicate prepared in Example 2.
[0019] Figure 4 These are scanning electron microscope photos of diatomaceous earth-based magnesium silicate prepared in Example 2, where (A) and (B) are at different magnifications.
[0020] Figure 5The nitrogen adsorption-desorption curve (A) and pore size distribution curve (B) of diatomaceous earth-based magnesium silicate prepared in Example 2 are shown in FIG.
[0021] Figure 6 (A) and (B) are respectively the magnesium silicate prepared in Example 2 for NH 4+ PO4 3- The adsorption capacity variation curve with time.
[0022] Figure 7 This is the X-ray diffraction curve of the magnesium ammonium phosphate / magnesium silicate filter residue of Example 3.
[0023] Figure 8 The mapping image (AD) and SEM image (E) of the magnesium ammonium phosphate / magnesium silicate residue obtained in Example 3.
[0024] Fig. 9 The sustained-release performance curves of Si element (A) and N, P element (B) of the magnesium ammonium phosphate / magnesium silicate filter residue recovered in Example 3 vary with time.
[0025] Fig.10 The XRD pattern of the filter residue obtained for Example 4. DETAILED DESCRIPTION
[0026] The following examples are used to illustrate the present invention but are not intended to limit the scope of the present invention. Embodiment 1:
[0027] The preparation method of diatomite-based three-dimensional structured nano magnesium silicate in this embodiment comprises the following steps: 1. Add 1g of diatomaceous earth into 40mL of ammonia solution and stir evenly at a speed of 200r / min.
[0028] 2. Dissolve 8 g of MgCl2·6H2O in 20 mL of deionized water and slowly add it dropwise to the suspension obtained in step 1 to obtain a mixed suspension.
[0029] 3. The mixed suspension obtained in step 2 is aged for 8 hours under hydrothermal conditions at 180° C., cooled, washed, filtered, and dried to obtain a diatomaceous earth-based three-dimensional magnesium silicate material.
[0030] Figure 1 This is the X-ray diffraction pattern of the sample prepared in Example 1. Figure 1 It can be seen that in 2 θ is 6.417 o , 19.443 o , 19.443 o ,34.159 o , 35.882 o and 60.024 oThe diffraction peaks at 2 correspond to the (002), (1-11), (-1-11), (132), (1-34) and (060) crystal planes of magnesium silicate in the chlorite phase (Mg-chlorite, JCPDS# 73-2376). θ is 6.417 o , 19.443 o , 19.443 o The diffraction peaks at 0.174 and 0.160 correspond to brucite phase (Brucite, JCPDS# 07-0239) magnesium hydroxide. In summary, the synthesized product is a mixture of brucite phase magnesium hydroxide and chlorite phase magnesium silicate.
[0031] Figure 2 The scanning electron microscope photograph of the sample prepared in Example 1. Figure 2 It can be seen that the composite material is disk-shaped as a whole, similar to the shape of diatomaceous earth. The micron-scale disk-shaped structure is self-assembled by nano-flower balls.
[0032] The upper and lower surfaces of the disk are flower-ball structures, while inside the three-dimensional structure is an array of nanopillars. Both the nanoflower balls and nanopillars are self-assembled from nanosheet structures. Figure 5 The nitrogen adsorption-desorption curve and pore size distribution curve of nitrogen-doped hydrothermal carbon@magnesium silicate composite material. As shown in Figure (A), the nitrogen adsorption-desorption curves are all type IV, indicating that the composite material has a mesoporous structure. The specific surface area calculated by the BET method is 201m 2 / g. There is an H3 type hysteresis loop at a relative pressure of about 0.4-1.0, which is attributed to the slit holes and wedge-shaped holes formed by the non-rigid aggregation of the thin-sheet structure, which is consistent with the SEM observation. The pore size distribution curve shows that the pore size of the composite material is concentrated in 0-20nm. Embodiment 2:
[0033] The difference between the preparation of magnesium silicate in this embodiment and that in embodiment 1 is that the amount of MgCl2·6H2O added in step 2 is 6 g, and other conditions are the same as those in embodiment 1. The diatomite-based magnesium silicate prepared in this embodiment is used to recover nitrogen and phosphorus in simulated wastewater.
[0034] The specific operation is: take 70mL of the prepared N and P wastewater, of which NH4 + PO4 3- The concentration is 100 mg / L, and then 0.02 g of diatomaceous earth-based magnesium silicate sample is added, mixed, magnetically stirred for 2 hours, and filtered to complete the adsorption recovery of N and P in the solution. The filter residue is dried at 50°C for standby use.
[0035] Figure 3 This is the X-ray diffraction pattern of the sample prepared in Example 2. θ is 6.417o , 19.443 o , 19.443 o ,34.159 o , 35.882 o and 60.024 o The diffraction peaks at correspond to the (002), (1-11), (-1-11), (132), (1-34) and (060) crystal planes of magnesium silicate in the chlorite phase (Mg-chlorite, JCPDS# 73-2376). Figure 1 It can be seen that the sample does not contain magnesium hydroxide phase. Figure 4 This is a scanning electron microscope image of the sample prepared in Example 2. Figure 4 It can be seen that the prepared magnesium silicate has a disk-like structure, which is self-assembled by nano flower balls. Figure 2 Similar. Combined Figure 2 and Figure 4 It can be seen that diatomaceous earth can play the role of a self-sacrificial template in the preparation of three-dimensional structured magnesium silicate.
[0036] Figure 5 The nitrogen adsorption-desorption curve (A) and pore size distribution curve (B) of the sample prepared in Example 2. As shown in Figure (A), the nitrogen adsorption-desorption curves are all type IV, indicating that the prepared magnesium silicate has a mesoporous structure. The specific surface area calculated by the BET method is 287 m 2 / g. There is an H3 type hysteresis loop at a relative pressure of about 0.4-1.0, which is attributed to the slit holes and wedge holes formed by the non-rigid aggregation of the thin sheet structure. Figure 4 The results of SEM observations are consistent with those of MgSiO2, and the pore size distribution curve shows that the pore size of the prepared magnesium silicate is concentrated in the range of 0-20 nm.
[0037] Figure 6 (A) and (B) are respectively the magnesium silicate prepared in Example 2 for NH 4+ PO4 3- The adsorption capacity of magnesium silicate samples varies with time. As shown in the figure, the adsorption rate of magnesium silicate samples on simulated N and P wastewater is fast at first and then slows down, and the adsorption equilibrium state can be reached within 30 minutes. 4+ PO4 3- The maximum adsorption capacities are 242 mg / g and 330 mg / g respectively. Embodiment 3:
[0038] Compared with Example 2, the difference is that the NH4 + PO4 3- The concentration was 500 mg / L, and other conditions were the same as in Example 2.
[0039] Figure 7The XRD pattern of the filter residue obtained after the sample was prepared for Example 3 to treat nitrogen and phosphorus wastewater. Figure 7 It can be seen that in 2 θ 15.0 o , 15.8 o , 16.5 o , 20.9 o , 21.5 o , 27.1 o , 30.2 o , 33.3 o , 38.2 o and 43.7 o The crystal diffraction peaks appearing at the pores correspond to the (110), (020), (011), (111), (021), (130), (012), (022), (231) and (042) crystal planes of magnesium ammonium phosphate in the struvite phase (Struvite, JCPDS# 15-0762). This indicates that the filter residue product is magnesium silicate / magnesium ammonium phosphate. The presence of magnesium ammonium phosphate phase indicates that magnesium silicate can achieve simultaneous recovery of N and P in water bodies through magnesium ammonium phosphate crystallization method. Magnesium ammonium phosphate is a nitrogen and phosphorus fertilizer that is slightly soluble in water. The obvious diffraction peaks of magnesium ammonium phosphate appearing in the product after adsorption indicate that the prepared magnesium silicate can effectively recover N and P in water bodies. And the recovered product is rich in N, P, and Si and can be used as a slow-release fertilizer.
[0040] Figure 8 The SEM image and mapping image of the recovered filter residue in Example 3. The flower ball-like structure unique to magnesium silicate can be observed in the image. In addition, a relatively regular long rod-like structure appears on the surface assembled from the flower ball structure. Figure 8 (D) The distribution diagram of P element clearly shows that the distribution of P element is enriched in the rod-like structure, and N and P elements are also distributed on the surface of magnesium silicate. Magnesium silicate is a flower ball structure, combined with Figure 7 Analysis shows that the rod-like structure obtained in Example 3 is magnesium ammonium phosphate. The distribution of Mg and N elements is basically the same, indicating that the Mg adsorption site will be partially NH4 + Combined to achieve NH4 + removal.
[0041] Fig. 9 The N, P, and Si element sustained release performance curves of magnesium silicate and recovered products prepared in Example 3 are as follows: 1 mol / L hydrochloric acid or sodium hydroxide solution was used to adjust the solution pH to 6, 7, and 8, respectively. 0.2 g of the magnesium silicate / magnesium ammonium phosphate residue obtained after adsorbing N and P in Example 3 was added to 50 mL of solutions with different pH values and allowed to stand at 25°C. Samples were taken after 24 h, 48 h, and 72 h, respectively, to test the N (NH 4+ )、P(PO43- )、Si(SiO3 2- ) element content. Fig. 9 It can be seen that under weakly acidic conditions (pH=6), the N, P, and Si slow-release performance of magnesium silicate / magnesium ammonium phosphate filter residue is the best, followed by weak alkalinity, and the worst is neutrality. At pH=6, after 3 days of slow release, the N, P, and Si slow-release concentrations of magnesium silicate / magnesium ammonium phosphate filter residue in the solution are 54 mg / L, 74 mg / L, and 258 mg / L, respectively. Embodiment 4:
[0042] Compared with Example 2, the difference is that the NH4 + The concentration is 100mg / L, PO4 3- The concentration was 200 mg / L. Other conditions were the same as those in Example 2.
[0043] Fig.10 The XRD pattern of the filter residue obtained in Example 4. Figure 7 Similarly, combined with X-ray diffraction characterization, it can be found that struvite phase (Struvite, JCPDS# 15-0762) magnesium ammonium phosphate also exists in the filter residue obtained at this time. Fig.10 The intensity of the crystal diffraction peak in the spectrum shown is Figure 7 There is a big difference. Fig.10 The diffraction peak intensity corresponding to the (020) crystal plane is much greater than Figure 7 The relative intensity change of this crystal plane diffraction peak indicates that the N and P concentration ratio will affect the growth of the formed magnesium ammonium phosphate phase crystal plane, but will not affect the type of the generated phase. Experimental example
[0044] The diatomaceous earth-based magnesium silicate material prepared in Examples 2 to 4 adsorbed the solution containing N and P, and the results are shown in the following table.
[0045]
[0046] At present, the main adsorbents used for the removal of N and P in water bodies include metal oxides / hydroxides; layered double hydroxides (LDH); zeolites; biomass charcoal and its composite materials. The removal effects of nano-metal oxide-modified diatomaceous earth and other composite materials prepared by the applicant in the early stage on nitrogen and phosphorus are similar to those reported in the literature. Taking MgO-modified diatomaceous earth as an example, when the dosage is 0.286g / L (0.02g / 70mL), the maximum adsorption capacity of MgO-modified diatomaceous earth for N and P is 89mg / g and 146mg / g, respectively, which is similar to the MgO adsorption materials reported in the literature. The reason why composite materials such as MgO-modified diatomaceous earth have low adsorption performance for N and P is that the main adsorption role in the composite material is played by nano-metal oxides or their oxygen-containing salts, and the diatomaceous earth, montmorillonite, activated carbon and other materials as the matrix have poor adsorption effects on N and P, resulting in the overall composite material The performance of removing N and P pollutants in water bodies is not high. The hydrothermally synthesized chlorite phase magnesium silicate is an amorphous mineral material with high adsorption activity. Its molecular formula is Mg6Si4O 10 (OH)8, whose molecular structure consists of a negatively charged 2:1 structural unit layer Mg3Si4O 10 (OH)2 and positively charged octahedral sheets Mg3(OH)6. Its molecular structure contains a large number of unstable Mg ions and magnesium hydroxyls, so it is suitable for precipitation to remove N and P through magnesium ammonium phosphate crystallization method. In addition, the prepared chlorite phase magnesium silicate has a large specific surface area (287m 2 / g), and in microscopic morphology, it is disc-shaped (with a diameter of about 30-40μm), and is self-assembled by nano-flower clusters. The pore structure constructed by it is suitable for the nucleation and growth of magnesium ammonium phosphate crystals. In summary, the hydrothermally synthesized amorphous chlorite phase magnesium silicate of the present invention is suitable for the synergistic removal of N and P in water bodies because it has abundant magnesium adsorption sites, a unique three-dimensional structure and a large specific surface area. The amorphous chlorite phase magnesium silicate itself is harmless to the environment and will not cause secondary pollution. The Si element in its structure is SiO3 2- The form can be slowly released into water or soil, so amorphous chlorite phase magnesium silicate is an environmentally friendly adsorption material and slow-release silicon fertilizer. The magnesium ammonium phosphate / magnesium silicate composite material formed after the adsorption of nitrogen and phosphorus can achieve the common slow release of N, P, and Si elements.
[0047] Although the present invention has been described in detail above by means of general description, specific implementation methods and tests, it is obvious to those skilled in the art that some modifications or improvements may be made to the present invention. Therefore, these modifications or improvements made without departing from the spirit of the present invention all fall within the scope of protection claimed by the present invention.
Claims
1. A method for recovering nitrogen and phosphorus from wastewater using diatomite-based three-dimensional structured nano magnesium silicate, characterized in that The steps include: The pH value of the wastewater containing nitrogen and phosphorus is adjusted to 8-9; diatomaceous earth-based three-dimensional structure nano magnesium silicate is added to the wastewater after the pH value is adjusted, stirred for 0.5-3h, and filtered to complete the adsorption and recovery of N and P in the solution wastewater; The diatomite-based three-dimensional structured nano magnesium silicate is prepared by using cheap diatomite as a self-sacrificial template to prepare chlorite phase magnesium silicate with high specific surface area and unique three-dimensional structure.
2. The method according to claim 1, characterized in that The preparation process of the diatomite-based three-dimensional structured nano magnesium silicate comprises the following steps: Step 1: Add diatomaceous earth into ammonia water and stir to form a diatomaceous earth and ammonia water suspension; Step 2: dissolving magnesium chloride in deionized water, and slowly adding the obtained magnesium chloride solution dropwise to the suspension obtained in step 1 to obtain a mixed suspension; Step 3: The mixed suspension obtained in step 2 is aged for 6 to 10 hours under hydrothermal conditions at 180 to 200° C., cooled, washed, filtered, and dried to obtain diatomaceous earth-based three-dimensional magnesium silicate.
3. The method according to claim 2, characterized in that: In step 1, the ratio of the volume of ammonia water to the mass of diatomaceous earth is 30-40:1 mL / g.
4. The method according to claim 2, characterized in that: In step 2, the mass ratio of MgCl2·6H2O to diatomaceous earth is 5-8:
1.
5. The method according to claim 1, characterized in that: The nitrogen-phosphorus concentration ratio in wastewater is 1:0.5-2.
6. The method according to claim 1, characterized in that: When the nitrogen concentration in the wastewater is ≤100 mg / L and the phosphorus concentration is ≤100 mg / L, the dosage of diatomaceous earth-based three-dimensional structured nano magnesium silicate is 0.3-0.7 g / L; when the nitrogen concentration in the wastewater is greater than 1000 mg / L or the phosphorus concentration is greater than 100 mg / L, the dosage of diatomaceous earth-based three-dimensional structured nano magnesium silicate is 0.7-3 g / L.
7. The method according to claim 1, characterized in that: After filtering, the filter residue is dried to obtain a magnesium ammonium phosphate / magnesium silicate composite material rich in the three elements of N, P and Si, which is further used in the preparation of slow-release fertilizers containing nitrogen, phosphorus and silicon.